Social Inclusion through Community Living: Current Situation, Advances and Gaps in Policy, Practice and Research - Šiška, Jan (Social Inclusion, 2018)
This article draws on the findings of the EU Framework 7 project DISCIT to explore the living situation of people with disabilities a decade after the adoption of the UN Convention on the Rights of Persons with Disabilities in nine European countries representing different welfare state models and different stages in the process of deinstitutionalisation. A review of the research literature, policy and available statistics was combined with interviews with key informants in each country to explore the current living situation, changes over time and the barriers to, and facilitators for change. The article focuses in particular on whether people are experiencing opportunities for social inclusion on an equal basis with others. Although a lack of available data hampered conclusions on living situation, it was clear that there had been some change in terms of policy and funding streams available to support community living. Some countries had moved slightly towards community living, while others reported more people in institutions or the development of bigger services in the community. There was evidence of continued inequality in the living situation and full inclusion of people with disabilities, with those with intellectual disability and psychosocial disabilities being the most affected. In terms of barriers (and consequently facilitators) there were three sources: 1) policy, 2) social care and support systems, and 3) awareness, attitudes and advocacy. The need to involve people with disabilities in policymaking and the need for a co-ordinated approach between all actors in the disability sector was seen as critical for achieving further change.